Targeting glycolysis: exploring a new frontier in glioblastoma therapy - Yang, Lu; Li, Sijia; Yu, Lei; Leng, Jiao; Li, Na (Frontiers in Immunology, 2025)
Glioblastoma(GBM) is a highly malignant primary central nervous system tumor that poses a significant threat to patient survival due to its treatment resistance and rapid recurrence.Current treatment options, including maximal safe surgical resection, radiotherapy, and temozolomide (TMZ) chemotherapy, have limited efficacy.In recent years, the role of glycolytic metabolic reprogramming in GBM has garnered increasing attention. This review delves into the pivotal role of glycolytic metabolic reprogramming in GBM, with a particular focus on the multifaceted roles of lactate, a key metabolic product, within the tumor microenvironment (TME). Lactate has been implicated in promoting tumor cell proliferation, invasion, and immune evasion. Additionally, this review systematically analyzes potential therapeutic strategies targeting key molecules within the glycolytic pathway, such as Glucose Transporters (GLUTs), Monocarboxylate Transporters(MCTs), Hexokinase 2 (HK2), 6-Phosphofructo-2-Kinase/Fructose-2,6-Biphosphatase 3 (PFKFB3), Pyruvate Kinase Isozyme Type M2 (PKM2), and the Lactate Dehydrogenase A (LDHA). These studies provide a novel perspective for GBM treatment. Despite progress made in existing research, challenges remain, including drug penetration across the blood-brain barrier, side effects, and resistance. Future research will aim to address these challenges by improving drug delivery, minimizing side effects, and exploring combination therapies with radiotherapy, chemotherapy, and immunotherapy to develop more precise and effective personalized treatment strategies for GBM.